Recovery of nitrogen cycling in riparian zones after stream restoration using δ15N along a 25-year chronosequence in northern Sweden - Maher Hasselquist, Eliza; Hasselquist, Niles; Sparks, Jed P.; Nilsson, Christer (Plant and Soil, 2017)
Swedish boreal streams were modified to transport timber by pushing boulders to stream sides, creating levees that disconnected streams from riparian areas. Many streams have since been restored and our goal was to understand how this affects riparian nitrogen (N) cycling.We compared the natural abundance of delta N-15 isotopes in foliage and roots of Filipendula ulmaria plus soils and litter along streams restored 2-25 years ago. We measured sources of N, potential immobilization of N, namely plant diversity and biomass, and the amount and sources of carbon (C) to determine if these were important for describing riparian N cycling.The delta N-15 of F. ulmaria foliage changed dramatically just after restoration compared to the channelized, disconnected state and then converged over the next 25 years with the steady-state reference.The disturbance and reconnection of the stream with the riparian zone during restoration created a short-term pulse of N availability and gaseous losses of N as a result of enhanced microbial processing of N. With increasing time since restoration, N availability appears to have decreased, and N sources changed to those derived from mycorrhizae, amino acids, or the humus layer, or there was enhanced N-use efficiency by older, more diverse plant communities.